The challenges and the possible solutions in fostering learner autonomy in esl classrooms: esl teachers’ voices - Saad, Sharina (GADING Journal for the Social Sciences, 2024)
The growing emphasis on learner-centered approaches in language teaching has led to increased consideration of autonomous learning. Although existing research has extensively explored the conceptualisation and evolution of learner autonomy, a notable gap exists in understanding the challenges faced by teachers in implementing practices to foster learner autonomy in tertiary-level ESL classrooms. This paper addresses this gap by examining the concept of learner autonomy, along with the associated challenges and possible solutions for implementation in tertiary-level English as a second language in Malaysia. Employing a qualitative methodology, specifically semi-structured interviews, the study aims to shed light on the reasons for integrating learner autonomy in the classroom and its significance from the teacher's perspective. The insights gained from this investigation are expected to inspire teachers to adopt effective methods, enabling learner involvement and empowering students to recognize their potential as confident, independent, and adult learners. By reshaping perspectives on learning modes, this study strives to guide learners towards a deeper understanding of knowledge with the supportive guidance of their teachers. The overarching goal is to offer a comprehensive view of the reasons behind using learner autonomy in the classroom, particularly in the Malaysian tertiary context, and provide practical suggestions for its effective integration. The paper concludes with recommendations drawn from its findings, intended to offer valuable insights for both novice teachers and policymakers as they navigate the evolving landscape of language education.